PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP GAYA HIDUP MAHASISWA ILMU KOMUNIKASI UNIVERSITAS ISLAM NEGERI SULTAN SYARIF KASIM RIAU - Darmawati Darmawati; Zul Ihsan (JIP: Jurnal Ilmu Pendidikan, 2024)
The development of technology, especially social media such as Instagram, has had a significant impact on people's lifestyles, especially among students. This study aims to explore the influence of Instagram social media on the lifestyle of Communication Science students at Sultan Syarif Kasim State Islamic University Riau. Using quantitative methods, this study collected data through questionnaires and interviews with students who are active users of social media. The results showed that Instagram social media not only influences social interaction but also shapes new consumption patterns and lifestyles. This study found that the use of Instagram can lead to positive or negative lifestyles, depending on how it is used. The findings are expected to provide insights for academics and society regarding the role of social media in shaping young people's lifestyles.